Modulation of Potassium Channel Activity in the Balance of ROS and ATP Production by Durum Wheat Mitochondria—An Amazing Defense Tool Against Hyperosmotic Stress - Trono, Daniela; Laus, Maura N.; Soccio, Mario; Alfarano, Michela; Pastore, Donato (Frontiers in Plant Science, 2015)
In plants, the existence of a mitochondrial potassium channel was firstly demonstrated about fifteen years ago in durum wheat as an ATP-dependent potassium channel (PmitoKATP). Since then, both properties of the original PmitoKATP and occurrence of different mitochondrial potassium channels in a number of plant species (monocotyledonous and dicotyledonous) and tissues/organs (etiolated and green) have been shown. Here, an overview of the current knowledge is reported; in particular, the issue of PmitoKATP physiological modulation is addressed. Similarities and differences with other potassium channels, as well as possible cross-regulation with other mitochondrial proteins (Plant Uncoupling Protein, Alternative Oxidase, Plant Inner Membrane Anion Channel) are also described. PmitoKATP is inhibited by ATP and activated by superoxide anion, as well as by free fatty acids (FFAs) and acyl-CoAs. Interestingly, channel activation increases electrophoretic potassium uptake across the inner membrane towards the matrix, so collapsing membrane potential (ΔΨ), the main component of the protonmotive force (Δp) in plant mitochondria; moreover, cooperation between PmitoKATP and the K+/H+ antiporter allows a potassium cycle able to dissipate also ΔpH. Interestingly, ΔΨ collapse matches with an active control of mitochondrial reactive oxygen species (ROS) production. Fully open channel is able to lower superoxide anion up to 35-fold compared to a condition of ATP-inhibited channel. On the other hand, ΔΨ collapse by PmitoKATP was unexpectedly found to not affect ATP synthesis via oxidative phosphorylation. This may probably occur by means of a controlled collapse due to ATP inhibition of PmitoKATP; this brake to the channel activity may allow a loss of the bulk phase Δp, but may preserve a non-classically detectable localized driving force for ATP synthesis. This ability may become crucial under environmental/oxidative stress. In particular, under moderate hyperosmotic stress (mannitol or NaCl), PmitoKATP was found to be activated by ROS, so inhibiting further large-scale ROS production according to a feedback mechanism; moreover, a stress-activated phospholipase A2 may generate FFAs, further activating the channel. In conclusion, a main property of PmitoKATP is the ability to keep in balance the control of harmful ROS with the mitochondrial/cellular bioenergetics, thus preserving ATP for energetic needs of cell defence under stress.